PENGARUH KUALITAS LAYANAN DAN CITRA TERHADAP KEPUASAN DAN LOYALITAS NASABAH BPR ARTOMORO SEMARANG (Students' Journal of Economic and Management, 2013)
This study analyzes the relationship between service quality and  corporate image on satisfaction and its consequences on customer loyalty. The object of this study is the Bank Perkreditan Rakyat (BPR) Artomoro Semarang. Problems in the study refer to the phenomenon of costumer decreasing BPRs of Central Java in the period 2008 – 2012. Models that were formulated in this study aim to provide a critical understanding of the concept and measurement of customer loyalty. The results of this study indicate that the quality of service has a positive and significant impact on customer satisfaction. Corporate image has a positive and significant impact on customer satisfaction. The effect of customer satisfaction on customer loyalty is positive and significant. While the development of hypotheses influence of service quality and corporate image were not had direct effect on loyalty. Keywords: Service Quality, Corporate Image, Customer Loyalty and Customer Satisfaction